Understanding weather and climate - Aguado, Edward Edward Aguado; Burt, James E., James E.Burt (Ameica: Pearson Education, 2015)
To interest students in learning about atmospheric processes and patterns, this book depicts meteorology and climatology using common events and inspired technological lessons. The Seventh Edition expands on global climate change coverage with new and distinctive sections on seas and climate in the Earth system. Each chapter also focuses on the human component of weather and climate, including high-interest weather-related risks that entice students to take the course while embracing the most recent research and challenges.
Includes bibliographical references and index.
Keywords: Atmospheric physics; Weather; Climatology